Reconciliation of Humanitarian Law and Human Rights Law in Armed Conflict - Ashri, Muhammad (Hasanuddin Law Review, 2019)
A common insight on human rights law as an instrument that aimed to protect the human dignity and values are often regarded to be separate from international humanitarian law. In relation to the norms, the difference between the two concepts related to the current conflict arise many debates. This paper reviews the common thread of the two international legal instruments. The connection between the two can be elaborated by explaining the concept; similarities and dissimilarities; and linking the basis for the establishment of legal instruments between human rights law and international humanitarian law. The results of research indicated that between international humanitarian law and human rights law have relevant rules applied in conflict situations. International humanitarian law as an instrument of international law is specifically applied in situations of armed conflict, whereas human rights law as a general instrument can be applied both in peace or conflict conditions. In a condition of armed conflict, international humanitarian law as a lex specialist is not widely interpreted to set aside human rights law. Human rights law is applied if facts or incidents exist in armed conflict that is contrary to human values.